KARAKTER MORFOMETRIK IKAN SIDAT DI BEBERAPA PERAIRAN PULAU HALMAHERA, MALUKU UTARA - Khamsiah Ahmad (Universitas Khairun, 2016)
Anguilla eel is one of the important economic values of fishery commodities both nationally and internationally. Eel is a unique organism that grows in the freshwater and migrated thousands of kilometers to open sea during lifetime for spawning. Information of biological and ecological aspects as an initiative data is necessary for domestication purposes. This study was carried out to identify eel species in Halmahera waters and to measure morphological characteristic of eel. Four sampling points of waters i.e. South Halmahera, East Halmahera, North Halmahera, and Ternate Island were chosen as known there are several rivers which suitable for eel habitat. 28 individuals were measured using Elis (1982) in Reveillac, et al (2009); and Effendie (1979) for body length (TL) and body weight (BW). The result shows that two species are found in Halmahera Waters namely Anguilla marmorata and Anguilla celebensis. Growth model is allometric negative which means body length is grower than body weight.Key words : Morphometric, Eel, Halmahera waters